Developmental systems of plasticity and trans-generational epigenetic inheritance in nematodes - Serobyan, Vahan; Sommer, Ralf J (Current opinion in genetics & development, 2017)
•Nematode phenotypic plasticity involves developmental switch genes.•Switch genes are regulated by chromatin remodeling and epigenetic mechanisms.•Trans-generational inheritance in C. elegans is induced by various stressors.•Epigenetic transmission of small RNAs is mediated by Argonaute proteins.•Genetics of organismal-environmental interactions are subject to selection. Several decades of research provided detailed insight into how genes control development and evolution, whereas recent studies have expanded this purely genetic perspective by presenting strong evidence for environmental and epigenetic influences. We summarize examples of phenotypic plasticity and trans-generational epigenetic inheritance in the nematode model organisms Pristionchus pacificus and Caenorhabditis elegans, which indicate that the response of developmental systems to environmental influences is hardwired into the organismś genome. We argue that genetic programs regulating these organismal–environmental interactions are themselves subject to natural selection. Indeed, macro-evolutionary studies of nematode feeding structures indicate evolutionary trajectories in which plasticity followed by genetic assimilation results in extreme diversity highlighting the role of plasticity as major facilitator of phenotypic diversification.